Rethinking Our Definition of Postoperative Success: A Comparative Analysis of Three Upper Eyelid Retraction Repair Techniques Using Novel Metrics to Capture Functional and Aesthetic Outcomes. Issue 1 (January 2018) - Evans, Jacob A.; Clark, Thomas J. E.; Zimmerman, M. Bridget; Allen, Richard C.; Nerad, Jeffrey A.; Carter, Keith D.; Shriver, Erin M.
Abstract : Purpose: To compare 3 upper eyelid retraction repair techniques and introduce novel metrics, which enhance the analysis of postoperative aesthetic outcomes. Methods: Retrospective review with Image J 1.48 digital analysis of patients who underwent repair of thyroid-related upper eyelid retraction at the University of Iowa from 1996 to 2014 via 1 of 3 surgical techniques, septum-opening levator recession with Muellerectomy, modified septum-preserving levator recession with Muellerectomy, and modified septum-preserving full-thickness blepharotomy, was conducted. Photographs were obtained preoperatively, 3 to 6 months postoperatively, and at last follow up (>6 months) and evaluated by digital image analysis (denoted by "i"). Outcome measures assessed were marginal reflex distance (iMRD1), temporal-to-nasal ratio, tarsal platform show (iTPS), pupil to visible eyelid crease, brow fat span (iBFS), tarsal platform show to brow fat span ratio (iTPS:iBFS), and tarsal platform show minimizing power (iTPS-minimizing power). Results: A total of 121 eyelids (28 septum-opening levator recession with Muellerectomy, 66 septum-preserving levator recession with Muellerectomy, and 27 septum-preserving full-thickness blepharotomy) from 74 patients were evaluated with a mean follow up of 24.2 months. There were no statistically significant differences between techniques in terms of iMRD1 or temporal-to-nasal ratio reduction at either time point (intertechnique p values of 0.17 to >0.99). The percentage of eyelids from subjects undergoing bilateral intervention that achieved a final iMRD1 between 2.50 mm and 4.50 mm was similar (intertechnique p value of 0.23), with no difference regarding the number of subjects demonstrating iMRD1 symmetry within 1 mm (intertechnique p value of 0.15). Though iTPS elongation was greater at 3 to 6 months with septum-opening compared with the combined septum-preserving techniques ( p value of 0.04), this difference was not maintained at final follow up ( p value of >0.99). There was no difference in terms of iTPS symmetry at time of final follow up (intertechnique p value of 0.69). The pupil to visible eyelid crease was unchanged in all techniques ( p values >0.99). Mean changes in iBFS at final follow up were −1.27 mm, −0.44 mm, and +0.55 mm for septum-opening levator recession with Muellerectomy, septum-preserving levator recession with Muellerectomy, and septum-preserving full-thickness blepharotomy ( p values of 0.01, 0.49, and >0.99, respectively). Mean iTPS:iBFS ratios at final follow up were not statistically different between techniques (intertechnique p value of 0.10) and no difference in symmetry was demonstrated (intertechnique p value of 0.47). Median values for iTPS-minimizing power were: −0.83, −0.93, and −1.01 for septum-opening levator recession with Muellerectomy, septum-preserving levator recession with Muellerectomy, and septum-preserving full-thickness blepharotomy, respectively (intertechnique p value of 0.54). Conclusions: Each technique appropriately lowered the eyelid and improved contour without intertechnique variability. Septum-preserving techniques demonstrated less iTPS elongation initially, but this difference was not maintained. The visible eyelid crease height (pupil to visible eyelid crease) remained stable in all techniques, indicating that the iTPS elongation seen with each technique was secondary to reduction in iMRD1 and the iBFS reduction seen with septum-opening levator recession with Muellerectomy was due to brow descent. No intertechnique differences in the amount of iTPS elongation relative to iMRD1 reduction (i.e., the novel iTPS-minimizing power) were seen. Given that each procedure evaluated yielded similar results, technique selection may be guided by surgeon experience and preference. Abstract : Image analysis of 3 anterior upper eyelid retraction repair techniques using standard and novel functional and aesthetic outcome measures revealed no significant long-term differences between septum-opening versus septum-preserving and layered versus full-thickness approaches.Supplemental Digital Content is available in the text.